Recent Advances in the Transition-Metal-Free Arylation of Heteroarenes - Uçar, Sefa; Daştan, Arif (Synthesis, 2021)
Transition-metal-free arylation reactions have attracted considerable attention for economic and environmental reasons over the past 40 years. In recent years, much effort has been made to develop efficient transition-metal-free approaches for the arylation of heteroarenes. Covering the literature from 2015 to early 2021, this review aims to provide a thorough overview of the synthetic and mechanistic aspects of these atom-economical and environmentally benign reactions.1 Introduction2 Arylation of Pre-functionalized Heteroarenes2.1 Arylation of Heteroaryl Halides2.2 Decarboxylative Arylation of Heteroarenes3 Direct C–H Arylation of Heteroarenes3.1 C(sp2)–H Arylation3.2 C(sp3)–H Arylation4 N-Arylation of Heteroarenes5 Summary and Outlook
Keywords: transition-metal-free reactions; arylation; heteroarenes; C–H functionalization